Analysis of community acceptability to COVID-19 vaccination in coastal communities of North Minahasa Regency - Kandou, Grace D.; Ratag, Budi T.; Kalesaran, Angela F. C.; Kandou, Priscilla C. (International Journal Of Community Medicine And Public Health, 2023)
Background: One of the important keys in dealing with COVID-19 is vaccination which can provide immunity to the community. The availability of an effective and safe vaccine certainly does not fully guarantee that the vaccination program will run well and give maximum results. In addition to vaccine distribution management which is quite complicated and must be done very carefully, the community's acceptability factor must be handled properly and carefully. The achievement of COVID-19 vaccination based on PCare Data from Wori health center and Tinongko health center as of January 8, 2022 was 61%. This illustrates that there are still many people who have not been vaccinated. The purpose of the study was to analyze the community's acceptability of the COVID-19 vaccination program in Wori District. Methods: The type of research to be carried out is quantitative research with an analytical observational design using a cross-sectional study approach. The research location is in 13 villages in Wori District. The research population is people who are in the administrative area of Wori District. Sampling was done by cluster sampling method using sample calculations obtained 376 respondents. Results: The results showed that there was a significant association between education level, employment status, and knowledge with community acceptability to COVID-19 vaccination. Conclusions: It is necessary to find an effective way to reach people with the most limited access to information in order to increase public acceptance of the vaccination program.